Experimental investigation of the geometry of geocell on the performance of flexible pavement under repeated loading - Banerjee, Sayanti; Manna, Bappaditya; Shahu, J.T. (Geotextiles and geomembranes, 2024)
To evaluate the benefit of geocells of different geometrical configurations for pavement application, full-scale instrumented model tests were performed on pavement sections reinforced with geocells of different geometrical configurations subjected to monotonic and repeated loading. The responses studied were stress distribution in different pavement layers, induced strains in geocell walls, and settlement characteristics. The reinforced sections exhibited a significant reduction in rut depth as well as localized stress concentration compared to the unreinforced section. The reduction in rut depth was found to be influenced by the geocell height as well as weld spacing. The geocell reinforcement was found to distribute the stresses in the subgrade and subbase layers more efficiently, thus reducing the stress concentration in these layers. The strain measurements were found to be higher at the bottom of the geocell walls indicating a higher confinement effect on a lower part of the geocell. In the field, mostly geocells of 356 mm weld spacing and 150 mm height (SW356-H150) are used. However, this study suggests that a geocell of 330 mm weld spacing and 100 mm height (SW330-H100) having approximately 30% lower cost compared to SW356-H150 is as effective in reducing the rut depth and localized vertical stress distribution. •Effect of weld spacing and heights of geocell reinforcement on pavement section is evaluated through full-scale model testing.•Study highlights that the reduction in rut depth is significantly influenced by the geocell height and weld spacing.•Geocell reinforcement reduces stress concentration in the subgrade and subbase layers by distributing stresses efficiently.•Higher strain measurements at the bottom of geocell walls indicate higher confinement at the lower part of geocell wall.•Study suggests use of SW330-H100 configuration of geocell as an economic alternative to conventional SW356-H150 configuration.